Enzootic Trypanosoma cruzi infection by Rhodnius prolixus shows transmission to humans and dogs in Vichada, Colombia - Cantillo-Barraza, Omar; Solis, Cesil; Zamora, Alexander; Herazo, Rafael; Osorio, María Isabel; Garcés, Edilson; Xavier, Samanta; Mejía-Jaramillo, Ana María; Triana-Chávez, Omar (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Rhodnius prolixus is considered the most relevant Trypanosoma cruzi vector in Colombia and Venezuela due it is responsible for domestic transmission in both countries. However, a wild population of this species is distributed in the eastern plains of the Orinoco region and Amazonia jungle, where its epidemiological importance has not been sufficiently elucidated. This study aimed to assess epidemiological parameters of T. cruzi transmission in the Department of Vichada, Colombia. Methods: We determined the characteristics of T. cruzi transmission using entomological studies in domestic and sylvatic ecotopes. We analyzed the T. cruzi infection in triatomine insects, identified blood meal sources, and conducted a serological determination of T. cruzi infection in scholar-aged children, domestic dogs, and wild hosts. Results: Fifty-four triatomine bugs, 40 T. maculata and 14 R. prolixus were collected in peridomestic and sylvatic ecotopes. Infected R. prolixus was observed in La Primavera, Santa Rosalia, and Cumaribo municipalities. All the T. maculata bugs were not infected. Serological analysis indicated that two of 3,425 children were T. cruzi positive. The seroprevalence in domestic dogs was 10,5% (49/465). Moreover, 22 synanthropic mammals were sampled, being Didelphis marsupialis the most common. TcI genotype was detected in seropositive dogs, R. prolixus, and D. marsupialis. Conclusion: The present work describes extra domestic R. prolixus and D. marsupialis in a sylvatic T. cruzi transmission cycle with transmission to humans and domestic dogs in Colombia's Vichada Department.